Manifestation of Sanctions Against Players of Forest and Land Burning in the Aspects of the Law on the Eradication of Corruption Criminal Acts - Vivi Arfiani; Jamri Jamri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2020)
Forest fires are mostly caused by land preparation activities for various forms of agriculture and forestry business (ranging from small scale such as shifting cultivation to large scale such as the development of Industrial Plantation Forest or HTI as well as oil palm, rubber plantations, etc.) which consequently often exacerbated by extreme climatic conditions such as a long dry season Law enforcement against forest and land burning actors is able to provide a deterrent effect for the perpetrators as well as to compensate for any losses arising from forest and land burning. Correct knowledge through systematic steps This type of research is classified into normative legal research or library research, providing boundaries through applicable laws and regulations in order to minimize all forms of threats and ri risk of pollution and environmental destruction for the preservation of life and ecosystems, an area exposed to extensive haze disasters to exceed national borders certainly requires a concrete effort to end the haze disaster caused by burning land and forests. The strategy to ensnare perpetrators of forest and land burning, both corporations and individuals, the State of Indonesia, ensnaring the law through a criminal law approach actually provides an alternative to uphold justice. Moreover, the impact of forest and land fires is not small. The Corruption Law Approach can be used as a new option to ensnare perpetrators of forest and land burning.